Grease - Shah, Raj; Woydt, Mathias; Tung, Simon C.; Rosenkranz, Andreas (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Everybody has made use of grease in their daily lives. The word "grease" originates from the early Latin word "crassus," meaning fat. For our purposes, in this Special Issue, we will be focusing on lubricating grease, for publication in the eponymous journal Lubricants. According to ASTM, lubricating grease may be defined as "a solid-to-semi-fluid product of dispersed thickening agents in a liquid lubricant". Other functional ingredients, such anti-wear and extreme pressure additives, may be included, with the overall goal of inducing special properties/functionalities. Grease is a very complex lubricant. We have never had a Special Issue focusing on this key product, and lubricating greases are often underrepresented in the technical literature. In recent years, there has been significant progress in research on greases, ranging from the specific chemical formulation of greases for special applications to how grease interacts with various surfaces, tribological advances in grease properties, new techniques for grease property measurements, etc. Recently, greases have also been evolving, as they and play a key role in the lubrication of electric vehicles. We aim to select the top research avenues and papers worldwide related to lubricating greases to form this compilation. This Special Issue wishes to be the first of its kind, and we plan to make this an annual exercise, where our compendium aims to discuss the latest developments worldwide encompassing all areas related to greases.